Effectiveness of technology in midwifery education for enhancing knowledge and clinical skills - Yohana Filiberta Lumu Ladjar; Ari Indra Susanti (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Multimedia has positively impacted knowledge transfer, emphasizing the importance of collaborative learning and interactive tools in improving educational outcomes. E-learning contributes significantly to knowledge transfer and skill enhancement among nurses and midwives. This study aims to determine the effectiveness of technology in midwifery education. This literature review uses a descriptive analysis approach. Article searches used keywords across three databases that met the inclusion criteria. As a result, 17 articles were selected as references for this study. The article specifically discusses the use of technology in education from three themes: knowledge enhancement, skill improvement, and clinical readiness of midwifery students. From the collected articles, six concluded that technology influences knowledge enhancement, ten agreed that technology can improve students' skills, and four believed that technology can increase students' clinical readiness. The study concludes that technology plays a vital role in equipping midwifery students with enhanced knowledge and skills and fostering their clinical practice readiness in maternal and child health care. AbstrakPemanfaatan multimedia menunjukkan dampak yang positif dalam transfer pengetahuan yang menekankan pentingnya pembelajaran kolaboratif dan alat interaktif dalam meningkatkan hasil pendidikan. E-learning memberikan kontribusi yang significan terhadap transfer pengetahuan dan peningkatan keterampilan diantara perawat dan bidan. Tujuan penelitian ini untuk mengetahui efektivitas penggunaan teknologi Pendidikan kebidanan. Literature review ini menggunakan pendekatan analisis deskriptif. Pencarian artikel dengan kata kunci pada 3 database yang memenuhi kriteria inklusi. Hasil penelitian didapatkan 17 artikel sebagai sumber rujukan dalam penelitian ini. Artikel ini membahas khusus tentang penggunaan teknologi dalam Pendidikan yang dilihat dari 3 tema yaitu peningkatan pengetahuan, peningkatan keterampilan dan kesiapan klinis mahasiswa kebidanan. Dari artikel yang dikumpulkan terdapat 6 artikel yang berkesimpulan bahwa teknologi mempengaruhi peningkatan pengetahuan, 10 artikel menyetujui bahwa teknologi dapat meningkatkan keterampilan peserta didik dan terdapat empat artikel yang meyakini bahwa teknologi dapat meningkatkan kesiapan klinis peserta didik. Simpulan penelitian ini teknologi berperan penting dalam mempersiapkan mahasiswa kebidanan untuk meningkatkan pengetahuan dan keterampilan, serta kesiapan praktik klinis dalam pelayanan Kesehatan Ibu dan Anak.Kata Kunci: kemampuan; pengetahuan; pendidikan kebidanan; teknologi